2017
DOI: 10.1186/s12909-017-1047-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of online versus alternative methods for training licensed health care professionals to deliver clinical interventions

Abstract: BackgroundOnline training is growing in popularity and yet its effectiveness for training licensed health professionals (HCPs) in clinical interventions is not clear. We aimed to systematically review the literature on the effectiveness of online versus alternative training methods in clinical interventions for licensed Health Care Professionals (HCPs) on outcomes of knowledge acquisition, practical skills, clinical behaviour, self-efficacy and satisfaction.MethodsSeven databases were searched for randomised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 33 publications
6
66
0
1
Order By: Relevance
“…For a high heterogeneity value (I 2 > 50%) [17], the recommended random-effects model was used in the meta-analysis for the pool weighted effect sizes [18]. The effect sizes were interpreted as 0.2 for a small effect, 0.5 for a moderate effect and 0.8 or greater for a large effect [8]. We used Review Manager (RevMan 5.3) [19] to carry out the metaanalyses in this review.…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For a high heterogeneity value (I 2 > 50%) [17], the recommended random-effects model was used in the meta-analysis for the pool weighted effect sizes [18]. The effect sizes were interpreted as 0.2 for a small effect, 0.5 for a moderate effect and 0.8 or greater for a large effect [8]. We used Review Manager (RevMan 5.3) [19] to carry out the metaanalyses in this review.…”
Section: Data Synthesismentioning
confidence: 99%
“…Through a metaanalysis, this study concluded that internet-based interventions were associated with positive effects compared to no interventions, but the effects and statistical heterogeneities were generally small compared to offline teaching. Richmond et al [8] then updated the evidence in this rapidly developing field by subdividing different formats of offline learning and comparing these formats to online learning. They focused their review, as well, on licensed healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Pursuing the same goal, we then conducted a forward search, using Google Scholar to identify studies that cited the included articles. We also consulted the reference lists of 12 earlier reviews and meta-analyses of online and distance education (Cook et al, 2008(Cook et al, , 2010Bernard et al, 2009;Means et al, 2009Means et al, , 2013Martin et al, 2014;Schmid et al, 2014;Liu et al, 2016;Margulieux et al, 2016;Taveira-Gomes et al, 2016;McKinney, 2017;Richmond et al, 2017). This second step of the literature search resulted in another three publications (Harned et al, 2014;Alnabelsi et al, 2015;Olson and McCracken, 2015) that met all the inclusion criteria.…”
Section: Publication Languagementioning
confidence: 99%
“…Therefore, it is important to link online content to course objectives and assessment of progress toward objectives to help the students "connect the dots" between the content with which students engage outside of face-to-face classroom time and its importance to their educational experience and clinical application (Foster et al, 2014). Since much clinical continuing education for licensed practitioners is online (Lawn, Zhi, & Morello, 2017;Richmond, Copsey, Hall, Davies, & Lamb, 2017), entry-level educators can help make this content delivery format familiar and workable for future practitioners.…”
Section: Implications For Ot Educationmentioning
confidence: 99%